An Emerging Awareness of Generation Z Students for Higher Education Professors - Giunta, Catherine (Archives of Business Research, 2017)
Generation Z, sometimes referred to as the iGeneration by demographers, marketers, and psychologists are a point of research by business professionals. However, little work has been done by academicians to research these students’ perceptions on various issues in a college setting. This study investigated Generation Z college students’ views regarding trust, use of social media, and related issues. The variables studied relate to current literature and key indicators representative of this generation. College students were the targeted participants. Students were surveyed in business courses after permission of the instructor was obtained. Subsequent interviews of faculty have begun. Quantitative surveying of faculty has been initiated. The findings indicate a group with high expectations for trust in others and with dependency on social media. The ramifications for professors will be discussed.